In silico molecular analysis of novel L-specific dehalogenase from Rhizobium sp. RC1 - Hanif Harisna, Azza (Malaysian Society for Microbiology, 2017)
Aims: This study presents the first structural model and proposed the identity of four important key amino acid residues,Asp13, Arg51, Ser131 and Asp207 for the stereospecific haloalkanoic acid dehalogenase from Rhizobium sp. RC1. Methodology and results: The enzyme was built using a homology modeling technique; the structure of crystallized LDEX YL from Pseudomonas sp. strain YL as a template. Model validation was performed using PROCHECK to generate the Ramachandran plot. The results showed 80.4% of its residues were located in the most favoured regions suggested that the model is acceptable. Molecular dynamics simulation of the model protein was performed in water for 10 nanoseconds in which Na+ was added to neutralize the negative charge and achieved energy minimization. The energy value and RMSD fluctuation of Cα backbone of the model were computed and confirmed the stability of the model protein. Conclusion, significance and impact of study: In silico or computationally based function prediction is important to complement with future empirical approaches. L-haloacid dehalogenase (DehL), previously isolated from Rhizobium sp. RC1 was known to degrade halogenated environmental pollutants. However, its structure and functions are still unknown. This structural information of DehL provides insights for future work in the rational design of stereospecific haloalkanoic acid dehalogenases